PENGARUH KEGIATAN ESKTRAKURIKULER ROHANI ISLAM (ROHIS) TERHADAP PENANAMAN NILAI KEAGAMAAN SISWA - Amalia Nurjannah; Adisa Oktarina (Raudhah - Proud To Be Professional, 2024)
This study aims to determine the effect of Rohani Islam (Rohis) extracurricular activities towards the cultivation of students' religious values. This research uses quantitative method. The research sample were 41 students. The data collection technique uses a questionnaire. The data analysis technique used in this research is simple linear regression. The results of the research show that based on the significance value (sig) from simple linear regression calculations the Sig value is 0.056 greater than 0.05. Therefore, it can be concluded that there is a significant influence between Rohis extracurricular activities and the cultivation of students' religious values.